Reinterpretasi Konseling Pastoral Keluarga Sebagai Strategi Pendeta dalam Upaya Preventif Perceraian Di GMIST Resort Bitung - Mourina Gracesia Suwuh; Brek, Yohan; Marulitua Agus Marpaung (PT. Giat Konseling Nusantara, 2024)
Marriage is considered an important foundation of life, but the reality of the increasing divorce rate in Indonesia shows serious challenges in maintaining family harmony. Pastors play a role as mediators in household conflicts, by implementing a spiritual approach and pastoral counseling that can help couples deal with their problems. This research was conducted using qualitative methods and describes pastoral counseling as a pastor’s strategy in divorce prevention efforts with a specific locus in the GMIST Resort Bitung area. In the context of the GMIST Resort Bitung, this study found that various inhibiting factors, such as lack of openness from couples and trust in pastors, hinder the effectiveness of pastoral counseling. Although pastors have implemented several strategies, such as regular visits and premarital counseling, their implementation is often inconsistent. This study shows the need for increased training and provision for pastors in pastoral counseling so that they can be more effective in helping families maintain their integrity and prevent divorce. Through a holistic approach and ongoing support, pastors can contribute significantly to maintaining family stability in the congregation